2002
DOI: 10.1200/jco.2002.06.171
|View full text |Cite
|
Sign up to set email alerts
|

Generation of T-Cell Immunity to the HER-2/neu Protein After Active Immunization With HER-2/neu Peptide–Based Vaccines

Abstract: Purpose: The HER-2/neu protein is a nonmutated tumor antigen that is overexpressed in a variety of human malignancies, including breast and ovarian cancer. Many tumor antigens, such as MAGE and gp100, are self-proteins; therefore, effective vaccine strategies must circumvent tolerance. We hypothesized that immunizing patients with subdominant peptide epitopes derived from HER-2/neu, using an adjuvant known to recruit professional antigen-presenting cells, granulocyte-macrophage colony-stimulating factor, would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
233
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 400 publications
(246 citation statements)
references
References 25 publications
4
233
0
6
Order By: Relevance
“…Analysis of the T cell responses induced on this trial demonstrated that intramolecular epitope-spreading also occurred at the level of the CD4 + T cell (9). However, data presented here demonstrates that immunity also spread to at least one additional breast cancer antigen besides HER-2/neu.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Analysis of the T cell responses induced on this trial demonstrated that intramolecular epitope-spreading also occurred at the level of the CD4 + T cell (9). However, data presented here demonstrates that immunity also spread to at least one additional breast cancer antigen besides HER-2/neu.…”
Section: Discussionmentioning
confidence: 66%
“…Epitope-spreading has also been described in cancer, occurring after certain immunotherapies such as vaccines. Although the endpoint of many clinical trials of cancer vaccines is the evolution of measurable immunity, recent evidence suggests that epitope-spreading may be a more significant predictor of effective immunity (9) or even of clinical response (21). The identification of both intra-and intermolecular humoral epitope-spreading epitope has not previously been reported following immunization with a cancer vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 Furthermore, naturally occurring, linked CTL and T h epitopes with improved immunogenicity are present in humans, such as human papillomavirus (HPV), 18,19 NY-ESO-1 (a cancer testis antigen), 20 and HER-2/neu. 21,22 One of the major mechanisms for the enhanced vaccine potency of long peptides is most likely that, unlike 8-mer to 10-mer CTL epitopes, these are not able to bind directly to MHC class I molecules, so their presentation to CTL precursors must follow processing by DCs. 2,23 Thus, long-peptide vaccines obviate binding to MHC class Iexpressing, nonspecialized APCs, which often results in transient CTL responses or tolerance.…”
Section: Therapeutic Vaccines Combined With Chemotherapymentioning
confidence: 99%